2008
DOI: 10.1007/s00216-008-2049-1
|View full text |Cite
|
Sign up to set email alerts
|

Catechol determination in compost bioremediation using a laccase sensor and artificial neural networks

Abstract: An electrochemical biosensor based on the immobilization of laccase on magnetic core-shell (Fe(3)O(4)-SiO(2)) nanoparticles was combined with artificial neural networks (ANNs) for the determination of catechol concentration in compost bioremediation of municipal solid waste. The immobilization matrix provided a good microenvironment for retaining laccase bioactivity, and the combination with ANNs offered a good chemometric tool for data analysis in respect to the dynamic, nonlinear, and uncertain characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…These nanoparticles used in electrochemical biosensors have the ability to provide a favorable microenvironment for biomolecules such as proteins to exchange electrons directly with an electrode [129]. Similarly, different enzyme based biosensors involving laccase [130, 131], tyrosinase [132], glucose oxidase [133, 134], horseradish peroxidase [135], and Fe 3 O 4 nanoparticles have been used for the construction of electrochemical biosensors. Tyrosinase electrode is also employed to monitor phenolic and catecholic compounds; it is one of the effective transducers for detection of phenols or catechols [85, 136, 137].…”
Section: Tyrosinase Biosensor Based On Interdigitated Electrodes mentioning
confidence: 99%
“…These nanoparticles used in electrochemical biosensors have the ability to provide a favorable microenvironment for biomolecules such as proteins to exchange electrons directly with an electrode [129]. Similarly, different enzyme based biosensors involving laccase [130, 131], tyrosinase [132], glucose oxidase [133, 134], horseradish peroxidase [135], and Fe 3 O 4 nanoparticles have been used for the construction of electrochemical biosensors. Tyrosinase electrode is also employed to monitor phenolic and catecholic compounds; it is one of the effective transducers for detection of phenols or catechols [85, 136, 137].…”
Section: Tyrosinase Biosensor Based On Interdigitated Electrodes mentioning
confidence: 99%
“…In the case of bioremediation, the use of an electrochemical biosensor based on the immobilization of laccase on magnetic core-shell (Fe 3 O 4 -SiO 2 ) NPs were combined with artificial neural networks for the determination of catechol concentration in it. The study results showed that combining an amperometric enzyme sensor and an artificial neural networks was effective because it presents sensitivity and is a robust method in the quantitative study of the composting system [158]. These and many more applications in bioremediation can be achieved with MNPs, and there is a whole world of possibilities awaiting.…”
Section: Bioremediationmentioning
confidence: 99%
“…In the reaction, hydroquinone (QH 2 ) as electron donor for the oxidized form of the enzyme, is mainly converted into quinone and/or free radical product (Q), and then is reduced on the surface of gold electrode at potentials below 0 V (vs. SCE), which efficiently shuttle electrons between laccase redox center and gold electrode surface in a dynamical equilibrium, leading to detectable response current [41]. The reaction equations of the redox process on the electrode surface are described as follows:…”
Section: Catalytic Reaction Mechanisms Of Biosensormentioning
confidence: 99%